Analisis Visual Konten Instagaram Kopi Kenangan dalam Membentuk Customer Engagement - Tabitha Bianca (CV. ULIL ALBAB CORP, 2024)
Currently, social media is the most searched media in the world, especially in Indonesian. According to a report published by Hootsuite in 2022, there are data on active social media users in Indonesia with 4.62 billion users. This research focuses on Kopi Kenangan, a food and beverage company that focuses on the coffee industry chain with a grab-and-go concept. Currently, Kopi Kenangan is a food and beverage company that is very popular with Indonesian people. Kopi Kenangan has an Instagram account with the account name (@kopikenangan.id). The descriptive method used in our research provides descriptive results and in-depth explanations. Secondary data is used as a data source.